Iron and Chromium Complexes Containing Tridentate Chelates Based on Nacnac and Imino- and Methyl-Pyridine Components: Triggering C-X Bond Formation - Morris, Wesley D.; Wolczanski, Peter T.; Sutter, Jörg; Meyer, Karsten; Cundari, Thomas R.; Lobkovsky, Emil B. (Inorganic Chemistry, 2014)
Nacnac-based tridentate ligands containing a pyridyl-methyl and a 2,6-dialkyl-phenylamine (i.e., (2,6-R-2-C6H3N=C(Me)CH=C(Me)NH(CH(2)py); R = Et, Et(nn)PMH; R = Pr-i, Pr-i(nn)PMH) were synthesized by condensation routes. Treatment of MN(TMS)(2)THFn (M = Cr, n = 2; M = Fe, Co, n = 1; TMS = trimethylsilane; THF = tetrahydrofuran) with Pr-i(nn)PMH) afforded Pr-i(nn)PMMN(TMS)(2) (1-M-iPr; M = Cr, Fe); Et(nn)PMMN(TMS)(2) (1-M-Et; M = Fe, Co) was similarly obtained. R(nn)PMFeBr (R = Pr-i, Et; 2-Fe-R) were prepared from FeBr2 and R(nn)PMLi, and alkylated to generate R(nn)PMFe(neo)Pe (R = Pr-i, Et; 3-Fe-R). Carbonylation of 3-Fe-R provided Pr-i(nn)PMFe(CO(neo)Pe)CO (4-Fe-iPr), and carbonylations of 1-Fe-R (R = Et, Pr-i) and 1-Ce-iPr induced deamination to afford R(nn)PIFe(CO)(2) (R = Pr-i, 5-Fe-iPr; Et, 5-Fe-Et), where PI is pyridine-imine, and kappa(2)-N,N-pyrim-pyrCr(CO)(4) (6-Cr-iPr), in which the aryl-amide side of the nacnac attacked the incipient PI group. Carbon-carbon bonds were formed at the imine carbon of the R(nn)PI ligand. Addition of [Pr-i(nn)PI(2-)](K+(THF)(x))(2) to FeCl3 generated Pr-i(nn)CHpy(2)Fe2Cl2 (7-Fe-iPr), and TMSN3 induced the deamination of 1-Fe-Et, but with disproportionation to provide [Et(nn)CHpy](2)Fe (8-Fe-Et). Ph2CN2 induced C-C bond formation with 1-Fe-iPr via its thermal degradation to ultimately afford Pr-i(nn)CHpy(2)(FeN=CPh2)(2) (9-Fe-iPr). The compounds were examined by X-ray crystallography (1-M-iPr, M = Cr, Fe; 1-Co-Et; 2-Fe-iPr; 4-Fe-iPr; 5-Fe-iPr; 6-Cr-iPr; 7-Fe-Et; 8-Fe-Et; 9-Fe-iPr), Mossbauer spectroscopy, and NMR spectroscopy. Structural parameters assessing redox noninnocence are discussed, as are structural and mechanistic consequences of the various electronic environments.